Lightweight Design of Reducer Housing of Large-sized Bridge Crane - Xiao Weizhong; Zhang Yanshan; Yan Shidang; Yu Feipeng; Zhi Yanfeng (Jixie chuandong)
Based on the strength and modal analysis,the lightweight design of gearbox housing is carried out by using the topological optimization method. Under the condition of meet the reliability of the gearbox,the housing weight is reduced about 15% after structural optimization. The rationality of housing improvement is verified through the contrast analysis on the reducer housing performance before and after optimization.